Perception of undergraduate pharmacy students on CBL learning environment - Abdullah, Nursyafiqah; Suratman, Suraya; Maniam, Sandra; Ali, Aida Azlina (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2023)
Introduction: An effective learning environment is important for proper academic and professional development of students. This can be assessed by exploring the students’ perception of the learning environment. This study aims to evaluate students’ learning responses and perceptions of their learning environment regarding case-based learning (CBL) implementation in the subject of pharmacology of second-year undergraduate pharmacy students. Methods: This is a descriptive cross-sectional study. The sample size is 120 second year students from the Pharmacy programme. The data was collected by using self- administered Dundee Ready Education Environment Measure (DREEM) inventory that consists of 50 items with 5 subscales of learning. Results: A total of 148 second-year pharmacy students participated in the survey and the response rate is 85. The majority of participants were female and the overall mean DREEM score in this study is 137.29, which indicates more positive learning environment than negative. Three items were identified as areas of concern which were an overemphasis on factual learning (mean=1.64), tutors being perceived as authoritarian (mean=1.97) and the presence of a cheating problem in the course (mean=1.86). In this study, no statistically significant association was found between each subscale of the perceptions of the learning environment and cumulative grade point average (p>0.05). Conclusion: Pharmacy students at UiTM Puncak Alam generally hold predominantly positive perceptions. However, there are identified problem areas that require improvement, emphasizing the need for more effective interventions.